COMPARISONS AMONG COMPUTED TOMOGRAPHIC FEATURES OF ADIPOSE MASSES IN DOGS AND CATS. Issue 1 (1st November 2016) - Spoldi, Elisa; Schwarz, Tobias; Sabattini, Silvia; Vignoli, Massimo; Cancedda, Simona; Rossi, Federica
Abstract : A better understanding of the CT features of different forms of canine and feline adipose tumors would be valuable for improving patient management and treatment. The purpose of this retrospective, cross‐sectional study was to describe and compare the CT features of pathologically confirmed lipomas, infiltrative lipomas, and liposarcomas in a sample of canine and feline patients. A total of 50 animals (46 dogs, four cats) and a total of 60 lesions (23 lipomas, 20 infiltrative lipomas, and 17 liposarcomas) were included in the study. Lipomas appeared as round to oval‐shaped ( n = 21), well‐marginated ( n = 20) fat‐attenuating lesions. Infiltrative lipomas appeared as homogeneous, fat‐attenuating masses but, unlike lipomas, they were most commonly characterized by an irregular shape (75%; P < 0.001), and linear components, hyperattenuating relative to the surrounding fat (100%; P < 0.05). Liposarcomas were represented exclusively by heterogeneous lesions with soft tissue attenuating components with a multinodular appearance (76.5%; P < 0.05). Regional lymphadenopathy ( n = 10) and amorphous mineralization ( n = 4) were also observed in association with liposarcomas. Computed tomography can provide useful information regarding disease location, extent, and involvement of the adjacent structures. Tumor definition and shape were the most useful parameters to differentiate between lipomas and infiltrative lipomas. The presence of a heterogeneous mass, with a multinodular soft tissue component and associated regional lymphadenopathy and mineralization, were features favoring a diagnosis of liposarcoma.